2017
DOI: 10.1098/rsos.170399
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leg-to-body ratio on male attractiveness depends on the ecological validity of the figures

Abstract: Leg-to-body ratio (LBR) predicts evolutionary fitness, and is therefore expected to influence bodily attractiveness. Previous investigations of LBR attractiveness have used a wide variety of stimuli, including line drawings, silhouettes, and computer-generated images based on anthropometric data. In two studies, community samples of heterosexual women from the USA rated the attractiveness of male figures presented as silhouettes and as detailed computer-generated images with three different skin tones (white, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…Subsequent work has typically used silhouettes based on photographs and has found a preference for average or above-average LBRs [ 19 , 20 ] (see also [ 21 – 23 ]). Some researchers have suggested that silhouettes lack ecological validity and may not accurately represent human body morphology [ 24 , 25 ], and more recent research has progressed to using naturalistic 3D-rendered CGI figures [ 26 , 27 ]. In a study of Japanese participants, Kiire [ 27 ] examined a wide range of LBRs using realistic rendered figures and, using a curve-fitting approach, found that the optimal attractiveness was very close to the population mean; in a similar study, Versluys & Skylark [ 25 ] found that, for heterosexual American women, the optimally attractive LBR for rendered male figures was approximately half a standard deviation above the population average.…”
Section: The Influence Of Leg-to-body Ratio Arm-to-body Ratio and Inmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent work has typically used silhouettes based on photographs and has found a preference for average or above-average LBRs [ 19 , 20 ] (see also [ 21 – 23 ]). Some researchers have suggested that silhouettes lack ecological validity and may not accurately represent human body morphology [ 24 , 25 ], and more recent research has progressed to using naturalistic 3D-rendered CGI figures [ 26 , 27 ]. In a study of Japanese participants, Kiire [ 27 ] examined a wide range of LBRs using realistic rendered figures and, using a curve-fitting approach, found that the optimal attractiveness was very close to the population mean; in a similar study, Versluys & Skylark [ 25 ] found that, for heterosexual American women, the optimally attractive LBR for rendered male figures was approximately half a standard deviation above the population average.…”
Section: The Influence Of Leg-to-body Ratio Arm-to-body Ratio and Inmentioning
confidence: 99%
“…Some researchers have suggested that silhouettes lack ecological validity and may not accurately represent human body morphology [ 24 , 25 ], and more recent research has progressed to using naturalistic 3D-rendered CGI figures [ 26 , 27 ]. In a study of Japanese participants, Kiire [ 27 ] examined a wide range of LBRs using realistic rendered figures and, using a curve-fitting approach, found that the optimal attractiveness was very close to the population mean; in a similar study, Versluys & Skylark [ 25 ] found that, for heterosexual American women, the optimally attractive LBR for rendered male figures was approximately half a standard deviation above the population average. (These authors also found that the effect of LBR was different for 3D-rendered images and silhouettes, confirming that studies of silhouette figures should be treated with some caution.)…”
Section: The Influence Of Leg-to-body Ratio Arm-to-body Ratio and Inmentioning
confidence: 99%
See 3 more Smart Citations